Risk assessment for work-related stress: a development study with UK hospital-based doctors - Rial-González, Eusebio (2000)
This thesis describes the development and implementation of a risk assessment strategy to deal with the problem of work-related stress in hospital-based doctors in the United Kingdom. Risk assessment is the initial phase of the risk management approach to work stress, and is followed by the 'translation' phase, risk reduction and evaluation of interventions.